2017
DOI: 10.1080/19390211.2017.1310784
|View full text |Cite
|
Sign up to set email alerts
|

A Polyphenol-Based Multicomponent Nutraceutical in Dysmetabolism and Oxidative Stress: Results from a Pilot Study

Abstract: To assess short-term efficacy and safety of a multicomponent nutraceutical (MCN) on dysmetabolism and oxidative stress, a pilot prospective observational study was performed on 21 individuals (12 men and 9 women) who took, for 60 days, 2 tablets per day of an MCN based on antioxidants and metabolism regulators: hydroxytyrosol (15 mg), maqui (300 mg), amla (200 mg), monacolin K (10 mg), berberine (245 mg), astaxanthin (0.5 mg), coenzyme Q10 (100 mg), and folic acid (200 mcg). On day 0 (T0) and day 60 (T60), all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…These intervention studies mainly showed beneficial effects of enriched olive oil on several key processes related to cardiovascular risk [49,50]. In other studies, it was shown the ability of a multicomponent nutraceutical containing HT to reduce free radicals and oxidized cholesterol, and to increase the serum antioxidant capacity [51]. An olive leaf extract (OLE) containing HT was used in a randomised, controlled, double-blind, crossover intervention trial to test its anti-inflammatory abilities in pre-hypertensive male volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…These intervention studies mainly showed beneficial effects of enriched olive oil on several key processes related to cardiovascular risk [49,50]. In other studies, it was shown the ability of a multicomponent nutraceutical containing HT to reduce free radicals and oxidized cholesterol, and to increase the serum antioxidant capacity [51]. An olive leaf extract (OLE) containing HT was used in a randomised, controlled, double-blind, crossover intervention trial to test its anti-inflammatory abilities in pre-hypertensive male volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…MqB treatment counteracted hyperlipidemia, hyperglycemia, and ROS production in metabolic syndrome patients. An MqB polyphenol-based-nutraceutical reversed low-grade-inflammation, oxidative stress, and atherosclerogenesis in pre-diabetic patients [ 223 ]. MqBE and purified anthocyanin consumption showed positive outcomes for post-stroke stress and depression in diabetic mice.…”
Section: Maqui Berriesmentioning
confidence: 99%
“…These extracts, which boost the activity of vitamin E present in feeds, may also exert the observed antioxidant activity by means of different mechanisms of action, including radical scavenging and enhancement of the expression of antioxidant enzymes [ 64 ]. Polyphenols have been extensively studied and reported to improve the oxidative status of cells in culture [ 65 , 66 ] but also animals (for references see [ 67 ]) and humans [ 68 , 69 ]. Our setup allowed the identification of an effective antioxidant concentration of ELIFE in a simple and fast way (total ROS stimulation and assessment time is about 4.5 h, of which 1 h is hands-on).…”
Section: Discussionmentioning
confidence: 99%